Analisis Kebijakan Alokasi Dana Kredit Terhadap Likuiditas, Profitabilitas Pada Koperasi Pegawai Republik Indonesia (KPRI) Puspita Bogor - Supriadi, Yoyon; Purwayanti, Indah (Jurnal Ilmiah Manajemen Kesatuan, 2015)
The purpose of this study was to determine liquidity and profitability, and their effect on the credit policy to liquidity and profitability in KPRI PUSPITA Bogor during the year 2009-2013. To achieve these objectives it has been done by compiling secondary data, especially financial reports and performing analysis on liquidity ratios and profitability ratios over the 5 years from 2009 to 2013. Moreover to find the relationship bemeen liquidity and profitability of the policies has been carried out Simple Correlation Analysis (bivariate correlation). The results showed that the credit turnover ratio in the period 2009-2013 rangedfrom 0.24 x or 1,513 days up to 0.35 x or 1,034 days, a decline in 2010 and in 2011 has increased again. Liquidity ratios ranged from 152.19% to 194.59%. The ratio of liquidity over the last 5 years shows that the financial performance of KPRI PUSPITA decreased. Profitability ratios ranged from 44.95% to 58.91%. The development of the profitability ratios for the last 5 years shows that the financial performance of KPRI PUSPITA decreased. Keywords: credit policy, liquidity, profitability